Effective learning during industry internship creates pathways to better corporate career for students of professional course a study of internship learning that contributes to enhancement of human capital in Indian context - Priyanita Bose; R.P. Banerjee; Sanchita Saha (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2023)
Corporate career requires competence, compatibility and adaptability apart from specific skills and values. The career becomes formidable and effective with a prior learning and experience through a similar corporate context prior to the entry to destination career. This is done through internship learning in business and corporate context in any country. Internship learning, thus enhances the quality and content of Human Capital in an individual professional. Finally contributing to the direct & indirect economic gain in a corporate organization and thereby the nation. Internship provides practical experience which enriches the knowledge and competence of the person. It provides hands on learning. Internship provides career related experience in his/her academic career both at undergraduate and postgraduate level. MBA students can do Internship can be done in any area. This study is on learning during internship and how effective it is for creating a corporate career in Indian context. Through the Internship process students develop good degree of knowledge of the corporate. One of the important things in the internship process is that students can get original information about the work and culture of the organization also how they operate in the market. In this entire practical learning process positive attitude is very important things to carry out entire work properly. Positive Attitude refers to affirmation towards any work with a view to undertake the work and taking it forward towards completion, based on the declared objective of the work. Through the internship learning students can learn hands on experiences, build their network with industry, can sharpen their professional capabilities and can learn the key areas that need to learn in the internship. Interns are destined to work with their values and ethics.